Addition to the genus Harmajaea (Agaricales, Pseudoclitocybaceae): a new and a known species from China - Qi, Yue; Yu, Xiao-Dan; Hou, Jian-Xuan; Guo, Hong-Bo; Yang, Rui-Heng; Xu, Ai-Guo (Phytotaxa, 2024)
A new species, Harmajaea xizangense, discovered in Tibet, China, is illustrated and described based on morphological and molecular data. Morphologically, H. xizangense is mainly characterized by its small pileus, relatively larger and longer spores, and unique geographical distribution. Phylogenetic analyses were performed based on nucleotide sequences of four molecular loci: the internal transcribed spacer (ITS), the nuclear ribosomal large subunit (nrLSU), the DNA-directed RNA polymerase II subunit 2 (RPB2), and the translation elongation factor (TEF1-α). The results indicated that the specimens belonged to the genus Harmajaea, occupying an isolated position in the phylogenetic trees. Furthermore, three collections of H. harperi are introduced for the first time from Liaoning Province of China. This study provides full descriptions, color illustrations, and phylogenetic trees of the two Harmajaea species.